Shiloh : a Kindred novel - Benton, Lori (Benton, Lori. Kindred novel, 2021)
December, 1795. The story of Ian Cameron and Seona, a former slave, continues. Seona and their son Gabriel are now living in Boston. Ian has stayed at Mountain Laurel, trying to make a life there with his wife Judith. But when tragedy strikes, Ian decides to return north with his young daughter. When Ian has the opportunity to obtain land near the frontier settlement of Shiloh, New York, he seizes the chance to make a new life with those he loves. Seona has taken her first tentative steps as a freewoman when Ian arrives, offering a second chance if she returns with him to Shiloh. As deep bonds are renewed, old hurts stand ready to threaten their future together.